Hotel assets: an analysis of brand attributes, franchise fees, hotel age and performance. (1st January 2013) - O'Neill, John W.; Dev, Chekitan S.; Hiromi, Yanagisawa
The selection of a hotel brand is an important consideration for asset managers and others. This study explored factors shaping the relationship between hotel asset managers and the brands with which they affiliate in an attempt to better understand the attributes that hotel brands bring to hotel assets. The particular attributes studied included how long a brand has existed, the franchise fees it exacts from property owners, guest satisfaction with the brand, and, at the individual property asset level, the age of the hotel facilities. By including franchise fees in the analyses of relationships between these attributes, we have broken new ground in this exploratory study, shedding light on the crux of the relationship between franchisees and the brands whose names they carry. To explore these relationships, we analysed a variety of data regarding the abovementioned variables to identify attributes that distinguish one hotel brand from another in terms of financial performance. Our results suggest that hotel property age, brand size, and guest satisfaction may be primary drivers of hotel performance, although the relationships between the factors are not all positive. On the other hand, brand age and franchise fees appear to have a much weaker relationship with hotel performance.